THE HISTORY OF HALKALI SCHOOL OF AGRICULTURE - Özgür YILDIZ (Fırat University, 2019)
Agriculture had always been one of the most significant dynamics of economy in the Ottoman State. Particularly the majority of the Muslims in the Empire gained their income from soil. After the Imperial Edict of Gülhane and the Royal Edict of Reform, the Ottoman State entered into a rapid downturn. This downturn maximized the seek for solutions. Abdulhamid the 2nd gave great efforts to halt the downturn. One of his solutions was to make reformist studies in agriculture. Opening Schools of Agriculture to carry out modern agricultural activities in The Ottoman State had been the most important agricultural policy of the period of Abdulhamid the 2nd. So, Sultan had Halkalı School of Agriculture opened in 1892 after all the preparations had been completed. This institute was among the most prominent institutes of the period. Halkalı School of Agriculture was founded together with the School of Veterinarians. The reason why it wasn’t able to be founded as an independent school of agriculture was the need for veterinarians due to epidemic animal diseases faced in the country. The school had a modern educational view for the age. Enrollment to the school was through an examination. The Empire put much value to these examinations. The students of the school were boarders from all over the country School teachers were Turkish, Greek and Armenians. The students were too, in parallel. The period of education was three years and the graduates came to prominent positions. As the students refrained from working in state works, three years of service was made obligatory. This study aims to briefly explain the history of Halkalı School of Agriculture in the light of Prime Ministry Ottoman Archive Documents.